On-chip inter-modal Brillouin scattering - Eric A. Kittlaus (Nature Portfolio, 2017)
Here, Kittlauset al. demonstrate stimulated inter-modal Brillouin scattering on-chip. Through this process, a Brillouin interaction couples light fields that propagate in distinct spatial modes of a Brillouin-active silicon waveguide, which may allow a variety of new processes in silicon photonics.